Doctor Appointment Checklist - Carolyn Wilken (EDIS)
As a patient, you will want to make the most of your doctor's visit. Take a few minutes to answer these questions prior to your doctor's visit. This will help you remember all that you want to ask and discuss with the doctor. (If you are a caregiver for an older adult, you may also want to review this checklist if you will assist the individual at the doctor's office.) This document is FCS2236, one of a series of the Department of Family, Youth and Community Sciences, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Publication date: June, 2005.